Paleogene to Neogene sequence stratigraphy and deepwater depositional systems in Kribi-Campo/Rio-Muni margin (Offshore Cameroon-Equatorial Guinea Margin) - Joseph Bertrand Iboum Kissaaka; Paul Gustave Fowe Kwetche; Jeannette Ngo Elogan Ntem; François Mvondo Owono; Marie Joseph Ntamak-Nida (Results in Earth Sciences)
2D seismic data and Gamma Ray logs were interpreted to document the Tertiary deepwater depositional system observed in the southern part of the Kribi-Campo sub-basin and the northern part of the Rio Muni basin, both basins separated by the Campo high. The sedimentary filling of both basins occurred with cyclicity during the Tertiary. The Paleogene filling exhibits at least three Seismic Unit Packages (SUP1 to SUP3) interpreted as some Feeder Channels-Lobe Complexes (FCLC). The units with Mass Transport Complexes (MTCs) are low amplitude and chaotic to transparent seismic facies. They are interpreted as mud-rich complexes. The units related to FCLC, features high to moderate amplitude with shingled oblique progradational clinoforms. The Neogene filling is dominated by some submarine Leveed-Channels Complexes associated to Lobes (LCCL) with low to moderate amplitude and concave-up mounded configuration. The well log analysis revealed three main electrofacies namely, shale, siltstone, and sandstone that were deposited in various depositional environments. Shale lithology are underlined by irregular, bell and bow gamma ray log motifs which may be deposited in inner shelf, tidal channels and channel-levees systems that are associated with transgressive to regressive depositional sequences. Sandstone and siltstone lithology are typified by funnel and cylindrical gamma ray log motifs that are deposited in prograding marine shelf fans and slope channels. Influenced by the high slope of paleotopography around the Campo High, the submarine channel-levee are confined to a western part of Kribi-Campo sub-basin. The FCLC shows large planar distribution, while the MTC are poorly structured.